A Case Series of Thromboelastography-Guided Anticoagulation in COVID-19 Patients with Inherited and Acquired Hypercoagulable States - Anthony V. Thomas; Kevin P. Lin; John E. Stillson; Connor M. Bunch; Jacob Speybroeck; Grant Wiarda; Hamid Al-Fadhl; Laura Gillespie; Mahmud Zamlut; Daniel H. Fulkerson; Rashid Z. Khan; Hau C. Kwaan; et al. (Case Reports in Medicine)
One of the complications of the novel coronavirus disease 2019 (COVID-19) is hypercoagulability. For this reason, patients presenting with COVID-19 are often put on therapeutic or intermediate anticoagulation upon hospitalization. A common issue of this anticoagulation is the progression to hypocoagulability resulting in hemorrhage. Therefore, monitoring the hemostatic integrity of critically ill COVID-19 patients is of utmost importance. In this case series, we present the cases of three coagulopathic COVID-19 patients whose anticoagulation was guided by thromboelastography (TEG). In each case, TEG permitted the clinical team to simultaneously prevent thrombotic and hemorrhagic events, a difficult task for COVID-19 patients admitted to the intensive care unit. The first two cases illustrate the utility of TEG to guide anticoagulant dosing for COVID-19 patients when the activated partial thromboplastin time (aPTT) is inaccurate. The first case was a severely ill COVID-19 patient with end-stage renal disease and a falsely elevated aPTT secondary to hypertriglyceridemia. The second case was a severely ill COVID-19 patient with chronic pulmonary disease who demonstrated a falsely elevated aPTT due to polycythemia and hemoconcentration. In both cases, TEG was sensitive to the hypercoagulability caused by the metabolic derangements which enabled the goal-directed titration of anticoagulants. The last case depicts a severely ill COVID-19 patient with an inherited factor V Leiden mutation who required abnormally high dosing to achieve therapeutic anticoagulation, guided by TEG. Hypercoagulopathic COVID-19 patients are difficult to anticoagulate without development of hypocoagulopathy. Treatment of these patients demands goal-directed therapy by diligent laboratory monitoring. This can be accomplished by the use of TEG coupled with aPTT to guide anticoagulation. This case series illustrates the necessity for active hemostatic monitoring of critically ill COVID-19 patients.